2022
DOI: 10.1007/s00018-022-04154-z
|View full text |Cite
|
Sign up to set email alerts
|

A20 and ABIN-1 cooperate in balancing CBM complex-triggered NF-κB signaling in activated T cells

Abstract: T cell activation initiates protective adaptive immunity, but counterbalancing mechanisms are critical to prevent overshooting responses and to maintain immune homeostasis. The CARD11-BCL10-MALT1 (CBM) complex bridges T cell receptor engagement to NF-κB signaling and MALT1 protease activation. Here, we show that ABIN-1 is modulating the suppressive function of A20 in T cells. Using quantitative mass spectrometry, we identified ABIN-1 as an interactor of the CBM signalosome in activated T cells. A20 and ABIN-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…A20 phosphorylation at serine 381 by an IκK leads to NF-κB pathway inhibition ( 11 ). In T and B cells, mucosa-associated lymphoid tissue transformation protein 1 (MALT1) mediates A20 cleavage following antigen receptor stimulation ( 29 ). The post-translational deubiquitylation modifications of A20 are related to K48- or K63-polyubiquitin chains ( 22 ).…”
Section: Regulation Of A20 and Its Relationship To Nf-κb Signaling In...mentioning
confidence: 99%
“…A20 phosphorylation at serine 381 by an IκK leads to NF-κB pathway inhibition ( 11 ). In T and B cells, mucosa-associated lymphoid tissue transformation protein 1 (MALT1) mediates A20 cleavage following antigen receptor stimulation ( 29 ). The post-translational deubiquitylation modifications of A20 are related to K48- or K63-polyubiquitin chains ( 22 ).…”
Section: Regulation Of A20 and Its Relationship To Nf-κb Signaling In...mentioning
confidence: 99%
“…Some studies reported that A20 regulated the NF-κB signaling pathway and downregulated proinflammatory cytokines expression ( 25 27 ). A20 negatively regulates CARMA3- and BCL10-mediated NF-κB activation via its deubiquitylation activity ( 28 ).…”
Section: Regulation Of Carma3mentioning
confidence: 99%
“…Upon surface receptor activation, CARMA/CARD, BCL10 and MALT1 form the CBM complex serving as a protein assembly platform for NF-κB activation [ 17 , 21 ]. TRAF6 (TNF receptor associated factor 6) and NEMO are further recruited to the CBM complex to induce a NF-κB activation cascade in response to TCR, BCR and GPCR activation [ 21 , 22 , 23 ]. Mutations in genes belonging to the CBM complex and consequent loss of MALT1 function are associated with human combined immunodeficiency [ 14 , 24 ].…”
Section: Introductionmentioning
confidence: 99%